Nonlinear Least Squares (NLS) Tracer Model - Siti Rahmawati; Sutawanir Darwis (Program Studi Statistika Unisba, 2009)
Tracer test is used to study possible temperature decline and cooling of production well during longtermre-injection through studying connection between injection and production well. Tracer testinvolve injecting a chemical tracer into a hydrological system and monitoring it’s recovery throughtime. Concentration tracer in production well is nonlinear model. Nonlinear Least Squares Method isproposed to estimate the tracer parameter, i.e. average fluid velocity in the channel and dispersioncoefficient, by using simulation data tracer concentration from production wells AH-4bis, AH-19, andAH-22 in Ahuacapan, Elsavador. The results of estimation are used for predicting thermalbreakthrough and cooling production well during long term re-injection.